2016
DOI: 10.1002/glia.23087
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic microglial clock system regulates interleukin‐6 expression

Abstract: Similar to neurons, microglia have an intrinsic molecular clock. The master clock oscillator Bmal1 modulates interleukin-6 upregulation in microglial cells exposed to lipopolysaccharide. Bmal1 can play a role in microglial inflammatory responses. We previously demonstrated that gliotransmitter ATP induces transient expression of the clock gene Period1 via P2X7 purinergic receptors in cultured microglia. In this study, we further investigated mechanisms underlying the regulation of pro-inflammatory cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 48 publications
3
65
1
Order By: Relevance
“…Despite the wealth of information regarding Rev-erbα in peripheral immune function, little is known about its role in innate immune responses in the brain. Microglia exhibit robust circadian clock function and inflammatory activation of microglia varies in a circadian manner (41,42). Thus, loss of rhythmic Rev-erbαmediated transcriptional repression could play a key role in the regulation of the microglial activation state, as demonstrated by our finding that microglial Iba1 volume changes with time of day in a Rev-erbα-dependent manner.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the wealth of information regarding Rev-erbα in peripheral immune function, little is known about its role in innate immune responses in the brain. Microglia exhibit robust circadian clock function and inflammatory activation of microglia varies in a circadian manner (41,42). Thus, loss of rhythmic Rev-erbαmediated transcriptional repression could play a key role in the regulation of the microglial activation state, as demonstrated by our finding that microglial Iba1 volume changes with time of day in a Rev-erbα-dependent manner.…”
Section: Discussionmentioning
confidence: 66%
“…Intrinsic clock genes are thought to cause circadian changes in microglial activity such as proinflammatory responses (Fonken et al, ; Hayashi et al, ; Nakazato et al, ). However, we suspected that NA is involved in the regulation of microglial synapse elimination during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study found that elevated IL-6 levels correlated with higher KYNA values in schizophrenia. This cytokine exerts an effect on different proinflammatory mechanisms in microglial cells [50,51] like microglia priming-i.e., the transition from resting to activated state [63]; regulation of the inflammatory response [64]; and overproduction of IL-6 in the aged brain [65]. Due to these microglial functions, authors pointed out that IL-6 was associated with KYNA production by increasing this metabolite in patients with schizophrenia [19].…”
Section: Il-6mentioning
confidence: 99%